Evaluating the Accumulation of Grain Mercury in Engineered Rice Lines Containing merA and merB Genes Under an Organic Mercury-Enriched Condition - Deyao Meng; Zhaoze Song; Jinyuan Liu; Liyang Ji; Chen Chen; Changhu Wang (Plants)
Rice is a critical crop for human sustenance worldwide. Food security has increasingly attracted public concerns, particularly due to heavy metal pollution, which adversely impacts crop yield and quality, with cadmium and mercury being the primary culprits. Excessive soil mercury not only hampers rice’s growth and development but also leads to a substantial accumulation in grains, posing a significant threat to human health. To mitigate the issue, low-mercury germplasms in rice were developed by expressing bacterial merA and merB genes, which convert mercury to less toxic forms from its most hazardous organic form: methylmercury. While previous evaluations of transgenic lines were typically conducted in environments mimicking inorganic mercury enrichment, studies on their performance in organic mercury-rich conditions, such as year-round rice planting paddies, remain limited. In this study, merA and merB transgenic rice lines were cultivated in organic mercury-contaminated soil to evaluate their grain mercury accumulation. Results showed a reduction in total grain mercury contents across three transgenic lines. Notably, one combined merA and merB line exhibited decreased organic mercury accumulation, and a reduction in total mercury levels in its grains, highlighting its breeding potential as a low-mercury rice germplasm for breeding programs.